Comprehensive Analysis of Respiratory Burst Oxidase Homologs (Rboh) Gene Family and Function of GbRboh5/18 on Verticillium Wilt Resistance in Gossypium barbadense - Chang, Ying; Li, Bo; Shi, Qian; Geng, Rui; Geng, Shuaipeng; Liu, Jinlei; Zhang, Yuanyuan; Cai, Yingfan (Frontiers in Genetics, 2020)
Respiratory burst oxidase homologs (Rbohs) play a predominant role in ROS production, which is crucial in plants growth, differentiation, as well as their responses to biotic and abiotic stresses. To date, however, there is little knowledge about the function of cotton Rboh genes. Here, we identified a total of 87 Rbohs from five sequenced Gossypium species (the diploids G. arboretum, G. raimondii, and G. australe, and the allotetraploids G. hirsutum and G. barbadense) via BLAST searching their genomes. Phylogenetic analysis of the putative 87 cotton Rbohs revealed that they were divided into seven clades. All members within the same clade are generally similar to each other in terms of gene structure and conserved domain arrangement. In G. barbadense, expression levels of GbRbohs in the CladeD were induced in response to a fungal pathogen and hormones (i.e., jasmonic acid and abscisic acid), based upon which the main functional member in CladeD was discerned to be GbRboh5/18. Further functional and physiological analyses showed that the knock-down of GbRboh5/18 expression attenuates plant resistance to Verticillium dahliae infection. Combined with the molecular and biochemical analyses, we found less ROS accumulation in GbRboh5/18-VIGS plants than in control plants after V. dahliae infection. Over-expression of GbRboh5/18 in G. barbadense resulted in more ROS accumulation than in control plants. These results suggest that GbRboh5/18 enhances cotton plants’ resistance against V. dahliae by elevating the levels of ROS accumulation. By integrating phylogenetic, molecular, and biochemical approaches, this comprehensive study provided a detailed overview of the number, phylogeny, and evolution of the Rboh gene family from five sequenced Gossypium species, as well as elucidating the function of GbRboh5/18 for plant resistance against V. dahliae. This study sheds fresh light on the molecular evolutionary properties and function of Rboh genes in cotton, and provides a reference for improving cotton’s response to the pathogen V. dahliae.